Lessons from Nutritional Labeling on the 20th Anniversary of the NLEA: Applying the History of Food Labeling to the Future of Household Chemical Labeling - Tobias J. Gillett (Washington University Journal of Law & Policy, 2011)
To remedy the defects of the current household chemical labeling system, Senator Al Franken of Minnesota and Representative Steve Israel of New York introduced legislation in the 111th Congress that would mandate labeling of “household cleaning products and similar products” with disclosure of all ingredients. This Note adopts that position as a starting point and proposes a new labeling scheme for all household chemicals modeled on the “Nutrition Facts” label mandated for food products. The Note reviews the history of food labeling regulation, examines present household chemical regulations, and proposes a new regulatory regime that learns from the successes and failures of food labeling past and present. Part II discusses the history of food and nutritional labeling since 1900. Part III features an overview of current household chemical labeling regulations. Part IV contains a brief introduction to some of the chemicals found in household products, including some of the known and suspected health and environmental concerns they may pose. Part V analyzes potential regulatory solutions to the problems presented by the current state of household chemical labeling and suggests some forms that a new labeling scheme should adopt.
Keywords: Food labeling; Household chemicals; Dietary Supplement Health and Education Act of 1994; Federal Insecticide, Fungicide and Rodenticide Act; Food Allergen Labeling and Consumer Protection Act of 2004; Nutrition Labeling and Education Act of 1990; United States; Food labelling